2022
DOI: 10.3390/jcm11030714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions to Improve the Anticholinergic Prescribing Practice in Older Adults: A Systematic Review

Abstract: Background: Pharmacotherapy in older adults is one of the most challenging aspects of patient care. Older people are prone to drug-related problems such as adverse effects, ineffectiveness, underdosage, overdosage, and drug interactions. Anticholinergic medications are associated with poor outcomes in older patients, and there is no specific intervention strategy for reducing drug burden from anticholinergic activity medications. Little is known about the effectiveness of current interventions that may likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
(245 reference statements)
0
6
0
Order By: Relevance
“…Currently, several studies that applied an MR separately in both community-dwelling patients and nursing-home residents reveal results aligned with this project, with a reduction of chronic medications, MRCI, and DBI [ 20 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 89%
“…Currently, several studies that applied an MR separately in both community-dwelling patients and nursing-home residents reveal results aligned with this project, with a reduction of chronic medications, MRCI, and DBI [ 20 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 89%
“…Attention to anticholinergic burden has increased over the last years, especially in elderly patients 28. Following this concern, several studies have assessed the role of pharmacists in deprescribing anticholinergic medicines, with most concluding a significant impact of interventions by the pharmacists 29. Although some studies reached no significant effect sizes, our study suggests a positive impact of pharmacists on the anticholinergic burden, although with a small effect size.…”
Section: Discussionmentioning
confidence: 54%
“…According to a systematic review of pharmacist interventions to improve anticholinergic prescribing practice in older people, medication reviews and education were the most commonly used interventions. [50]. A systematic review found that pharmacist-led interventions that involved collaboration with medical practitioners reduced anticholinergic drug burden more than other interventions [44].…”
Section: Discussionmentioning
confidence: 99%